Magnifying perspectives: contributions to history, a festschrift for Robert Ross - Pesa, I; Gewald, J (African Studies Centre Leiden, 2017)
Magnifying Perspectives is a festschrift for Robert Ross, Emeritus Professor of African History at Leiden University. The contributions have been written by the students and colleagues of Robert Ross, reflecting his broad-ranging thematic and geographical research interests. Individual chapters cover topics such as slavery, gender and gossip, but also reflect an eye for detail in narrating about mosquitoes, semaphores and pineapples. Big themes such as race and imperialism are tackled by paying attention to language, material objects and the powerful role of individuals in shaping history. Contributions on all parts of the African continent, from Nigeria and Mali to Angola and South Africa, as well as Britain and Australia are included. This book attempts to do justice to the unique approach to African history which Robert Ross advocated, an approach which emphasises the complexity and dignity of human nature by placing it at the centre of historical writing.